2002
DOI: 10.1590/s0103-50532002000300006
|View full text |Cite
|
Sign up to set email alerts
|

The Raman Spectrum of the Squarate (C4O4-2 ) Anion: An Ab Initio Basis Set Dependence Study

Abstract: O perfil de excitação Raman do anion esquarato, C 4 O 4 -2 , foi calculado por métodos ab initio no nível de teoria Hartree-Fock utilizando a Teoria de Resposta Linear (TRL) para seis frequências de excitação: 632,5, 514,5, 488,0, 457,9, 363,8 e 337,1 nm. Um total de cinco conjuntos de funções de base (6-31G*, 6-31+G*, cc-pVDZ, aug-cc-pVDZ e bases de Sadlej) foi investigado visando comparar o desempenho da base 6-31G*, em termos de convergência numérica dos resultados e custo computacional, com os dos demais c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Helgaker and colleagues attributed the discrepancies observed between their calculations and experimental results to the lack of inclusion of electronic correlation (all calculations were done at the HF level), experimental errors, and neglect of anharmonicities. At this level, de Miranda and Vazquez 5 presented a study of the effect of basis sets on the excitation profile of squarate (C 4 O −24) anion for six excitation frequencies ranging from 632.5 to 337.1 nm. They concluded that all sets tested (i.e., 6‐31G*, 6‐31+G*, cc‐pVDZ, aug‐cc‐pVDZ, and Sadlej's polarizability basis set 6, 7) have correctly reproduced the main spectroscopic features of the squarate Raman spectrum, showing that relative Raman intensities are much less dependent on the basis set than are absolute ones.…”
Section: Introductionmentioning
confidence: 99%
“…Helgaker and colleagues attributed the discrepancies observed between their calculations and experimental results to the lack of inclusion of electronic correlation (all calculations were done at the HF level), experimental errors, and neglect of anharmonicities. At this level, de Miranda and Vazquez 5 presented a study of the effect of basis sets on the excitation profile of squarate (C 4 O −24) anion for six excitation frequencies ranging from 632.5 to 337.1 nm. They concluded that all sets tested (i.e., 6‐31G*, 6‐31+G*, cc‐pVDZ, aug‐cc‐pVDZ, and Sadlej's polarizability basis set 6, 7) have correctly reproduced the main spectroscopic features of the squarate Raman spectrum, showing that relative Raman intensities are much less dependent on the basis set than are absolute ones.…”
Section: Introductionmentioning
confidence: 99%